A Study on English Vocabulary Size of Students Majoring in International Natural Science Education, Yogyakarta State University - Syafrianto, Syafrianto; Wulandari, Maria (Jurnal Inovasi Pendidikan MH Thamrin, 2018)
The current study is an attempt to discover the vocabulary size of students majoring in International Natural Science Education and the developmental pattern of their vocabulary size. The proposed research questions are: (1) What are the vocabulary sizes of students of international natural science education? and (2) Is their vocabulary size different across levels (freshmen, sophomore and junior)? To achieve the research aim, a cross-sectional research design was used. The total number of 79 students from three semesters studying in International Natural Science Education participated in the study. The instrument used was a Vocabulary Size Test developed by Nation and Beglar (2007). A descriptive statistic and an inferential statistics One-Way ANOVA continued by a pos-hoc test (Scheffe) were run in order to answer the proposed research questions. The results of computation revealed that the vocabulary size was 5,271-word families for the freshmen level, 6,142-word families for the sophomore level and 6,524-word families for the junior level. Based on the result of inferential statistics One-Way ANOVA, the student’s vocabulary size across levels are different. The F-ratio indicates that the difference between these groups was 7,369 in the level of significance 0,001. Furthermore, based on the Scheffe test, the significant difference lies between semester 2 and semester 4. Meanwhile, the difference of the vocabulary size between semester 4 and semester 6 was found to be less significant. In general, it can be concluded that there is a difference on the development of student’s vocabulary size reflected by the result of statistical analysis. The developmental pattern of students’ vocabulary size seems to be positive since the higher the level, the larger the students’ vocabulary size.